Flexible Low-Dose GnRH Antagonist Protocol Is Effective in Patients With Sufficient Ovarian Reserve in IVF - Zhang, Dan; Xia, Lan; Xu, Huihui; Chen, Qian; Jin, Bailing; Zhang, Aijun; Xu, Bufang (Frontiers in Endocrinology, 2018)
Gonadotropin-releasing hormone antagonist (GnRH-ant) has been shown to negatively influence endometrial receptivity. Reducing the GnRH-ant dose during controlled ovarian stimulation (COS) when using a GnRH-ant protocol may be beneficial to embryo implantation. However, whether or not the minimum daily GnRH-ant dose should be individualized remains uncertain. In this retrospective study, we aimed to elucidate the feasibility and effectiveness of moderately reducing the daily GnRH-ant dose to 0.125 mg, and then adjusting the dose to 0.25 mg based on subsequent luteinizing hormone (LH) levels. Of the 434 patients analyzed in this study, 209 received our new flexible low-dose GnRH-ant protocol (Group 1) and 225 received a conventional GnRH-ant protocol with a fixed daily dose of 0.25 mg (Group 2). Furthermore, 105 and 114 cycles from groups 1 and 2 received fresh embryo transfer. In Group 1, 30 patients whose dose of 0.125 mg GnRH-ant was adjusted according to their LH levels and 179 patients who received consistently low doses were further divided into subgroups 1 and 2, respectively. Neither the number of retrieved oocytes and available embryos nor the implantation rate, clinical pregnancy rate, and ongoing pregnancy rate significantly differed between the two groups. However, GnRH-ant dose and stimulation duration were much lower and shorter in Group 1 than in Group 2 (P < 0.05). Subgroup 1 exhibited higher basal follicle-stimulating hormone (FSH) and lower antral follicle count (AFC) than subgroup 2 significantly. The number of retrieved oocytes and available embryos were lower in subgroup 1 than in subgroup 2 (6.83 ± 3.28 vs. 11.83 ± 4.82, 2.93 ± 1.86 vs. 4.99 ± 3.46, respectively, p < 0.05), while more cancelled cycles for pre-ovulation occurred in subgroup 1 than in subgroup 2 (3/30 vs. 1/179, p < 0.05). The results showed that the flexible low-dose GnRH-ant protocol was as effective as the conventional fixed-dose GnRH-ant protocol with 0.25 mg per day for most patients with normal ovarian reserve. This retrospective analysis and the small sample size are the main limitations of this study, and a large sample RCT trail will be carried out in future.